2018
DOI: 10.1016/j.bbadis.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

MitoQ protects dopaminergic neurons in a 6-OHDA induced PD model by enhancing Mfn2-dependent mitochondrial fusion via activation of PGC-1α

Abstract: Parkinson's disease (PD) is characterized by the degeneration of dopaminergic neurons in the substantia nigra compacta (SNc). Although mitochondrial dysfunction is the critical factor in the pathogenesis of PD, the underlying molecular mechanisms are not well understood, and as a result, effective medical interventions are lacking. Mitochondrial fission and fusion play important roles in the maintenance of mitochondrial function and cell viability. Here, we investigated the effects of MitoQ, a mitochondria-tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 44 publications
2
55
0
1
Order By: Relevance
“…We found that 6‐OHDA exposure reduced PGC1α mRNA expression and its protein expression in cytosol (Figures b and b). This is consistent with previous reports that observed that mitochondrial Complex I inhibitors such as 6‐OHDA reduced PGC1α expression (Xi et al, ). Our data also show that FA upregulates PGC1α mRNA and protein expression in lesioned animals, which is once again suggestive of the potential of FA to alleviate mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…We found that 6‐OHDA exposure reduced PGC1α mRNA expression and its protein expression in cytosol (Figures b and b). This is consistent with previous reports that observed that mitochondrial Complex I inhibitors such as 6‐OHDA reduced PGC1α expression (Xi et al, ). Our data also show that FA upregulates PGC1α mRNA and protein expression in lesioned animals, which is once again suggestive of the potential of FA to alleviate mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…Similar direction of changes was seen when the intensity of mitochondrial staining with MitoTracker Red was compared ( Figure 2). This phenomenon might be correlated with the fact that several studies have shown that 6-OHDA affects mitochondrial fusion and fission causing an imbalance in mitochondrial dynamics, and it is proven that it may contribute to the pathogenesis of neurodegenerative diseases [61][62][63]. Previous studies demonstrated that 6-OHDA (albeit at a high concentration of 150 μM) caused a loss of cell viability and mitochondrial depolarization [55,64].…”
Section: Discussionmentioning
confidence: 97%
“…The mitochondrial membrane potential (MMP) was measured using tetramethyl rhodamine ethyl ester (TMRE) staining, and mitochondrial reactive oxygen species (ROS) production using MitoSox Deep Red staining, as previously described [33]. Primary neurons were incubated with 10 nmol/L TMRE (T669, Life Technologies, Carlsbad, CA) or 5 nmol/L MitoSox (M36008, Invitrogen, Carlsbad, CA) for 0.5 h. Then, the cells were washed 3 times with Hanks' Balanced Salt Solution to remove the medium.…”
Section: Analysis Of Mitochondrial Functionmentioning
confidence: 99%